2003
DOI: 10.1002/app.13165
|View full text |Cite
|
Sign up to set email alerts
|

Compositional analysis of biodegradable polyphosphoester copolymers using nmr spectroscopic methods

Abstract: ABSTRACT:The chemical composition and quantitative molar ratios among all components of biodegradable polyphosphoester copolymers of dl-lactide and ethylphosphate were determined by a comprehensive set of NMR spectroscopic methods. The polyphosphoester copolymers studied were synthesized using condensation polymerization of oligomeric dl-lactide prepolymers and ethyl dichlorophosphate. Conclusive identification of the chemical shift patterns of all functional groups in the copolymers required additional NMR me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Its excellent biocompatibility and biological resorbability afford it extensive applications in biomedical fields, including sutures, bone fixation materials, drug-delivery microspheres, and tissue engineering. [1][2][3][4][5][6] To improve the performance of PLA, especially to promote its cell adhesion, many PLA copolymers, such as poly(lactic acidglycolic acid), 7 PLA-poly(ethylene glycol), 8 PLApoly(phosphate ester), 9 and poly(lactic acid-amino acid), 10 have been developed via the copolymerization of other functional molecules with lactic acid (LA) or lactide.…”
Section: Introductionmentioning
confidence: 99%
“…Its excellent biocompatibility and biological resorbability afford it extensive applications in biomedical fields, including sutures, bone fixation materials, drug-delivery microspheres, and tissue engineering. [1][2][3][4][5][6] To improve the performance of PLA, especially to promote its cell adhesion, many PLA copolymers, such as poly(lactic acidglycolic acid), 7 PLA-poly(ethylene glycol), 8 PLApoly(phosphate ester), 9 and poly(lactic acid-amino acid), 10 have been developed via the copolymerization of other functional molecules with lactic acid (LA) or lactide.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically-modifying PLA is another attractive route to imparting inherent ame retardancy, and while the literature is lean of such examples, reports of PLA with demonstrated or inferred ame retardancy exist. PLA copolymerized 27 or chainextended 28,29 with phosphorus compounds, for example, are desired for their potential biological activity, and such reports hint at potential ame retarding characteristics. FR-PLA via sidechain modication with halogen or phosphorus functionalities is plausible with the recent introductions of functionalized lactide monomers, [30][31][32][33][34] although, to the best of our knowledge, such techniques have not been applied to developing FR-PLA formulations.…”
Section: Introductionmentioning
confidence: 99%
“…The result was consistent very well with the fact that all three isomers of BPGF were random, chemically bonded into polymer chains. Chaubal24 et al obtained the same result as they studied the chemical structure of a polymer resulting from poly( DL ‐lactide) and EDP, they also got three peaks (−1.6, −1.9, −2.4 ppm) in 31 P spectrum of polymer. They studied this phenomenon by model compound and concluded that these results were due to different bonding sequence of P‐O bond.…”
Section: Resultsmentioning
confidence: 61%